Kajian Hukum Penataan Wilayah Sekitar Kawasan Bendungan Jatigede Dalam Pembentukan Kawasan Ekonomi Khusus (KEK) Dalam Perspektif Otonomi Daerah Kaitannya Dengan Pendapatan Asli Daerah (PAD) Kabupaten Sumedang - Prihastuti, Diane (Jurnal Hukum Media Justitia Nusantara, 2022)
The current legislation (positive law) does not reflect the implementation of the existing constitution. Distribution of authority between the centre and the regions in the management of economic resources in the laws and regulations and government regulations. At the level of implementation of Law No. 32 of 2004 and Government Regulations it has not accommodated some of the needs of the government management system and the needs of government management systems in the era of regional autonomy. This model of cooperation between regions initiated by several district / city regional groups certainly needs to be accompanied by the establishment of clear authority in facilitating, coordinating and mediating from the Central or Provincial Governments. Based on the objectives, principles, and norms and rules contained in the Law, coupled with applicative and democratic conditions, the distribution of the weight of authority at every level of government and between regions. The administrative decentralization approach in the formulation of the Law on Regional Government in Indonesia and also political decentralization which gives authority and strength to the regions is very necessary so that a balance occurs in the formulation or structuring of central and regional authorities. The method of approach used in this study is a normative juridical approach discussing the doctrine of the doctrine of principle of law in law. In general research is distinguished between data directly from the community called primary data or basic data where as those obtained from library materials commonly called secondary data. The legal study of the arrangement of Special Economic Zones in the Jatigede Dam buffer zone is expected to be able to increase the Sumedang District’s Original Revenue. With the enactment of the regional autonomy policy, the regional government is expected to be able to develop the potential that exists in Sumedang district, tackling any existing problems by conducting planning, management and supervisory functions. Programs that can increase the original income of the Sumedang Regency need to get support and facilitation between the central and regional governments and there is a need to make clear legal rules so that a positive impact on the economic capacity of a region can be realized. Perundang-undangan yang ada saat ini (hukum positif) belum mencerminkan implementasi dari konstitusi yang ada. Pembagian kewenangan antara pusat dan daerah dalam pengelolaan sumber daya ekonomi di dalam peraturan perundang-undangan dan peraturan pemerintah. Pada tataran pelaksanaan Undang-undang No 32 Tahun 2004 dan Peraturan Pemerintah belum menampung beberapa kebutuhan sistem manajemen pemerintah dan kebutuhan sistem manajemen pemerintahan di era otonomi daerah. Model kerjasama antar daerah yang diprakarsai oleh beberapa kelompok daerah kabupaten/kota ini tentu perlu diiringi dengan penetapan kewenangan yang jelas dalam memfasilitasi, mengkoordinasi dan memediasi dari Pemerintah Pusat atau Provinsi. Dengan berpatokan pada tujuan, azas-azas, dan norma serta aturan yang ada dalam Undang-undang, ditambah dengan syarat aplikatif dan demokratis, distribusi bobot kewenangan di setiap jenjang pemerintahan dan antar daerah. Pendekatan desentralisasi administratif dalam perumusan Undang-undang Pemerintahan daerah di Indonesia dan juga desentralisasi politik yang memberikan otoritas dan kekuatan kepada daerah sangat diperlukan sehingga terjadi keseimbangan dalam perumusan atau penataan kewenangan pusat dan daerah. Metode Pendekatan yang digunakan dalam penelitian ini adalah metode pendekatan yuridis normatif membahas doktrin-doktrin atau asas-asas dalam ilmu hukum. Dalam penelitian pada umumnya dibedakan antara data yang langsung dari masyarakat dinamakan data primer (atau data dasar), sedangkan yang diperoleh dari bahan-bahan pustaka lazimnya dinamakan data sekunder. Kajian hukum penataan Kawasan Ekonomi Khusus pada kawasan penyangga (buffer zone) Bendungan Jatigede diharapkan mampu meningkatkan Pendapatan Asli Daerah Kabupaten Sumedang. Dengan diberlakukannya kebijakan otonomi daerah maka pemerintah daerah diharapkan mampu mengembangkan potensi-potensi yang ada pada Kabupaten Sumedang, menanggulangi setiap permasalahan yang ada dengan cara melakukan perencanaan, pengelolaan dan fungsi-fungsi pengawasan. Program yang dapat meningkatkan pendapatan asli daerah Kabupaten Sumedang perlu mendapatkan dukungan serta fasilitasi antara pemerintah pusat dan daerah dan perlunya membuat suatu aturan hukum yang jelas sehingga berdampak positif terhadap kemampuan ekonomi suatu daerah dapat terwujud.